Tantangan Pengajaran Bahasa Indonesia Sebagai Sarana Pembentuk Karakter Bangsa - Khudlory Khudlory (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This paper discusses the culture and character of the nation's current begins to drop. The decline of the nation's character is currently characterized by a variety of cases that arise in the midst of society, such as the fight between students, between students, sex crimes, vandalism-destruction, corruption, and many other cases. Various of the above cases can only be addressed through the establishment and development of national character. To establish and build the character of the nation toward a better one that needs to be addressed is through education that uses a cultural approach. Only through a cultural approach potential learners will be developed. The cultural approach in this case can be done through the teaching of Indonesian language. The cultural approach include learning methods, learning models, and teacher professionalism in teaching, and is no less important is the awareness of teacher to constantly improve their capabilities and skills. Through the capabilities and skills of the least qualified teachers will be implemented to the student about how to build the character of the nation in school.